1989
DOI: 10.1111/j.1346-8138.1989.tb01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Sarcoidosis Showing Multiple Papular Eruptions with Keratotic Plugs

Abstract: A 26-year-old woman developed 249 discrete papules on her lower extremities. Twenty-three of them had keratotic plugs. Histologic examination demonstrated granulomatous foci consisting of epithelioid cells and a epidermal invagination which was disrupted at the base and lateral sites. This invagination was considered to represent transepithelial elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…There have been few cases of cutaneous sarcoidosis showing keratotic plugs. 2,3 All of those cases showed solitary keratotic papules, and no plaque with aggregated comedones as in the present case has been reported. As a pathomechanism of plug formation, Higari et al 2 reported transepithelial elimination, which was not observed in our case.…”
Section: Cutaneous Sarcoidosis With Aggregated Comedones In a Young Woman Possibly Associated With Cosmetic Laser Treatmentsupporting
confidence: 60%
See 1 more Smart Citation
“…There have been few cases of cutaneous sarcoidosis showing keratotic plugs. 2,3 All of those cases showed solitary keratotic papules, and no plaque with aggregated comedones as in the present case has been reported. As a pathomechanism of plug formation, Higari et al 2 reported transepithelial elimination, which was not observed in our case.…”
Section: Cutaneous Sarcoidosis With Aggregated Comedones In a Young Woman Possibly Associated With Cosmetic Laser Treatmentsupporting
confidence: 60%
“…2,3 All of those cases showed solitary keratotic papules, and no plaque with aggregated comedones as in the present case has been reported. As a pathomechanism of plug formation, Higari et al 2 reported transepithelial elimination, which was not observed in our case. It is possible that the plugs formed as a result of follicular obstruction as in comedones induced by widespread sarcoidal granulomas.…”
Section: Cutaneous Sarcoidosis With Aggregated Comedones In a Young Woman Possibly Associated With Cosmetic Laser Treatmentsupporting
confidence: 60%
“…Sarcoidosis with histopathologic evidence of transepithelial elimination was previously considered a rare phenomenon, with six cases described in the English literature . Additionally, three cases have been described in the foreign literature, but are not detailed in this article .…”
Section: Discussionmentioning
confidence: 98%
“…Cutaneous sarcoidosis with histopathologic evidence of transepithelial elimination was previously considered a rare phenomenon, with six cases described in the English literature to date . We begin by describing a case of cutaneous sarcoidosis with histopathologic evidence of transepithelial elimination and also complete a review of the English literature regarding this phenomenon.…”
mentioning
confidence: 99%